Dim lights, bright prospects: Purple phototrophic bacteria-driven industrial wastewater treatment for biomass resource recovery at low light intensities - Ojima Z. Wada (14155734) (2024)
The utilization of purple non-sulfur bacteria (PNSB) has emerged as an eco-friendly approach to biological wastewater treatment. However, the high energy demands associated with artificial lighting have been a major drawback to scaling up this biotechnology. Thus, this study investigates the phototrophic treatment of gas-to-liquid wastewater (COD=6.1 g·L−1) and biomass recovery using PNSB mixed culture at low light intensities (9.6 and 17.6 W·m−2). The non-axenic culture achieved high pollutant removal rates (347–453 mgCOD·L−1d−1 and 22–31 mgTN·L−1d−1), effective biomass concentrations (1.6–1.8 gVSS·L−1), yields (0.5–0.8 gCODbiomass·gCODremoved−1) and moderate PNSB selectivity (32–35 %), favouring the higher light intensity (HLI). Recovered biomass chiefly consisted of protein (43–48 %), lipids (33–34 %), carbohydrates (8–10 %), poly-3-hydroxybutyrate-co-3-hydroxyvalerate (2–10 %), bacteriochlorophyll (1.2–1.3 %), carotenoids (0.4–0.6 %), and coenzyme Q10 (0.001–0.004 %). Amino acid characterization showed superior quality compared to soybeans, maize, and seaweed, containing essential amino acids for livestock. Lipid characterization revealed that biomass consisted chiefly of mono-unsaturated C16-C18 fatty acids with biodiesel potential and nutritional value. Further analysis revealed the biomass was fortified with micro and macro nutrients suitable for soil enrichment. Overall, this study highlights PNSB's ability to treat high-strength industrial wastewater and upcycle nutrients into valuable substances at dim intensities, facilitating a multiple-stream circular economy in resource-scarce and solar-dim regions. Other Information Published in: Process Safety and Environmental Protection License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.psep.2024.12.037